Pemberdayaan Karang Taruna Dalam Meningkatkan Potensi Desa Wisata Melalui Sadar Wisata Di Desa Bancangan Sambit - Suci, Siti Nur Kurnia; Fathoni, Tamrin (Journal of Community Development and Disaster Management, 2023)
Karang Taruna is a forum for the development of the younger generation, which grows on the basis of awareness and a sense of social responsibility for the community, especially the younger generation in the Baancang village area or equivalent social community. which is primarily engaged in social welfare. The existence of youth who are members of youth organizations in the village becomes a core forum as a unifying paradigm and generates interest in talent in order to empower youth, this cannot be separated from the encouragement of the local government and the community so that youth youth organizations become productive forums for village progress and sustainability of the village of Baancang. . Judging from the natural conditions, the village of Baancang has a variety of natural resources that should be maintained and developed and can even be used as a land of income that has economic value for individuals and local community groups, a beautiful environment, and the achievement of promising developments. This is the basis for the problem to be solved in an effort to achieve the expected goals. One of the villages that is rich in natural potential but has not been optimized. Based on the partner's problems, the problems can be solved by several approaches, namely observation and socialization of the program and objectives: lectures, discussions, evaluations. The workshop activities have a very good impact and provide awareness of the importance of increasing tourism villages in Baancang village. In this way, there will be workshops on tourism awareness for youth groups, rangers, village officials as well as enthusiastic communities in increasing the potential of tourism villages in Baancang Village.